2021
DOI: 10.3390/ani11072060
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Palmer Drought Severity Index Data and Tuberculosis-like Lesions Occurrence in Mediterranean Hunted Wild Boars

Abstract: In the Iberian Peninsula, the prevalence of tuberculosis differs for each region and for different wild disease hosts and the region affected by a Mediterranean climate will be the most affected. The Mediterranean Iberic regions have a favourable ecosystem for the development of Mycobacterium tuberculosis complex agents, where habitat, population dynamics, and climate (especially drought) are important factors affecting the high prevalence of tuberculosis in the wild boar population. Our objective was to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Previous studies in Mediterranean environments have reported TBL percentages of between 50-75% in wild boar populations, which corroborates our ndings (Vicente et al 2006(Vicente et al , 2007(Vicente et al , 2013Naranjo et al 2008;Barroso et al 2020). These oscillations may be related to climatic events such as droughts and its indirect consequences, which increase the prevalence of TB in the subsequent season (Vicente et al 2013;Barroso et al 2020;Abrantes et al 2021). In Spain, the driest years recorded were 2005 and 2017 (< 500mm http://www.aemet.es/), corresponding to a high TBL prevalence during the following year.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in Mediterranean environments have reported TBL percentages of between 50-75% in wild boar populations, which corroborates our ndings (Vicente et al 2006(Vicente et al , 2007(Vicente et al , 2013Naranjo et al 2008;Barroso et al 2020). These oscillations may be related to climatic events such as droughts and its indirect consequences, which increase the prevalence of TB in the subsequent season (Vicente et al 2013;Barroso et al 2020;Abrantes et al 2021). In Spain, the driest years recorded were 2005 and 2017 (< 500mm http://www.aemet.es/), corresponding to a high TBL prevalence during the following year.…”
Section: Discussionsupporting
confidence: 91%
“…Each study site was assigned the herd prevalence of the geographical unit where it was located. Aridity was shown to be a risk factor for TB in wild ungulates in the markedly seasonal Mediterranean ecosystems of the Iberian Peninsula by influencing their aggregation, particularly at watering sites during the dry season (Triguero-Ocaña et al, 2020;Vicente et al, 2013;Abrantes et al, 2021). To assess the effect of this risk factor, the Global Aridity Index (GAI) was included as an independent variable in the model.…”
Section: Discussionmentioning
confidence: 99%
“…6), a region characterized by moderately high aridity (Fig. 1), where host aggregation at watering points was shown to be a risk factor for TB (Triguero-Ocaña et al, 2020;Vicente et al, 2013;Abrantes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between drought and M. bovis infection or disease have been detected in other multihost systems. In a large study of Mediterranean wild boars ( n = 3,923), which are known bTB reservoirs, the occurrence of drought and increasing drought severity were significantly associated with increased occurrence of TB-like lesions ( 45 ). Another study investigating risk factors for bTB in cattle in Great Britain showed a positive association between atmospheric dryness and areas of high risk for M. bovis infection ( 46 ).…”
Section: Discussionmentioning
confidence: 99%